El Perú y la guerra del Paraguay 1864-1870 - Cristóbal Aljovín de Losada (Nuevo mundo - Mundos Nuevos, 2009)
This paper studies the Peruvian position during the war of Paraguay in a period of wars in the Americas. That conflict occurred while Chile, Bolivia, Peru and Ecuador were fighting a Spanish fleet. This fact generated an American-Republican discourse in Peru. At first, Peru, Chile and, to a lesser extent, Bolivia, coordinated their actions aiming to find a negotiated solution to the conflict. Such position was favorable to Paraguay. Later on, the Peruvian position begins to change with the coming of a new President, with a different position regarding his predecessor. This paper ends highlighting the relationships between domestic and foreign policy, and the dynamics of Chile, Peru and Bolivia in relation to Argentina and Brazil.